The Influence of Digital Marketing Strategy, Product Quality, and Price on Purchase Decisions for Imported Second-Hand Clothing - Muhammad Rafli Firdaus; May Dadu; Jefry Romdonny (Almana : Jurnal Manajemen dan Bisnis, 2026)
The growing popularity of imported second-hand clothing (thrifting) has been driven by digitalization, shifting consumer lifestyles, and increasing awareness of affordable and sustainable fashion, leading to changes in consumer purchasing behavior. This study aims to examine the influence of digital marketing strategy, product quality, and price on consumers’ purchase decisions at OB Second Cirebon. A quantitative approach was employed using a survey method, with data collected through structured questionnaires distributed to consumers who had purchased products within the past year. The sample was determined using purposive sampling based on specific criteria relevant to the study. Data analysis was conducted using multiple linear regression supported by SPSS, preceded by validity, reliability, and classical assumption tests, as well as hypothesis testing using t-test and F-test. The results indicate that digital marketing strategy, product quality, and price have a positive and significant effect on purchase decisions, both individually and simultaneously. Among these variables, product quality emerges as the most influential factor in shaping consumer decisions. These findings suggest that optimizing digital marketing activities, maintaining consistent product quality, and setting appropriate pricing strategies are essential for enhancing consumer purchase decisions and supporting the growth of the thrift fashion industry.